2021
DOI: 10.2337/db20-1008
|View full text |Cite
|
Sign up to set email alerts
|

Dedicator of Cytokinesis 5 Regulates Keratinocyte Function and Promotes Diabetic Wound Healing

Abstract: Cutaneous wound healing is a fundamental biologic and coordinated process, and failure to maintain this process contributes to the dysfunction of tissue homeostasis, increasing the global burden of diabetic foot ulcerations. However, the factors that mediate this process are not fully understood. Here, we identify the pivotal role of dedicator of cytokinesis 5 (Dock5) in keratinocyte functions contributing to the process of skin wound healing. Specifically, Dock5 is highly upregulated during the proliferative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Protein ubiquitination has been shown to play diverse regulatory roles in the context of wound healing [ 28 , 29 ]. USP family proteins, including USP15, are key mediators of protein deubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ubiquitination has been shown to play diverse regulatory roles in the context of wound healing [ 28 , 29 ]. USP family proteins, including USP15, are key mediators of protein deubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dedicator of cytokinesis protein (DOCK) also plays a key role in regulating keratinocyte function and promoting skin wound healing. [ 60 ] Specifically, DOCK5 regulates keratinocyte adhesion, migration, and proliferation and influences ECM deposition by laminin‐332/integrin signaling. In addition, fibroblasts showed premature senescence, abnormal morphology, and decreased ability to migrate and proliferate in diabetic wounds.…”
Section: Ros Homeostasis and Relevance Of Ros In Diabetic Woundsmentioning
confidence: 99%
“…Dedicator of cytokinesis 5 (Dock5) is one of the candidate molecules known to be implicated in proteinprotein interactions (20). Recently, Hua Qu et al found Dock5 regulated keratinocyte migration by promoting ubiquitination of ZEB1 to activate laminin-332/integrin signaling (21).…”
Section: Delayed Re-epithelialization and Collagen Depositionmentioning
confidence: 99%